Development of English Composition Writing Ability Using B-SLIM (Bilash’s Success-guided Language Instruction Model) of Third Year Students, Faculty of Languages, Souphanouvong University - BOUNTHAVONG, Oudalon; SENGPHACHITH , Somphong; SROINAM, Rapeeporn (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research were to study and compare the English composition writing ability of third year students before and after learning using B-SLIM, and to study the students’ attitude towards teaching English composition writing using B-SLIM. The sample consisted of 27 third year students who enrolled in English writing courses in the first semester of the academic year 2019-2020 of Faculty of Languages, Souphanouvong University. They were selected using cluster random sampling. The research was an experimental research with a one group pretest-posttest design. The research instruments were 6 lesson plans, and an English paragraph writing ability test and a students’ attitude questionnaire. The experiment lasted 6 weeks, 4 hours a week, 24 hours for all. The mean, percentage, standard deviation and t-test for dependent sample were used for data analysis. The result of this research were as follows: The students’ pretest score on English composition writing ability was 46.03 percent and the posttest was 76.70 percent. The mean score on the posttest was higher than that of the pretest. The students’ English composition writing ability was significantly different at the .01 level. The students’ attitude toward teaching English composition writing using the B-SLIM was at a good level.